Non-linear electron structures in high-current plasma lens - Goncharov, A.; Gubarev, S.; Dobrovolskii, A.; Litovko, I.; Protsenko, I. (Вопросы атомной науки и техники, 2000)
We describe the experimental investigations of the dispersion characteristics of the electron oscillations excited owing to drift instability in high-current plasma lens (PL). The experiments were carried out using the heavy ion beams of copper or carbon with energy up to 18 keV, beam current up to 0,5 A, duration 100 mks produced by the MEVVA kind ion source. It is shown that the noise electrostatic potential oscillations arise in middle plane of the lens under passing ion beam through plasma lens. These noises in range of 0,25÷2 MHz have a regular structure with stationary amplitude depending on ion beam current value. On their background a comparable low-intensity high-frequencies noises in range 20÷50 MHz is also observed. We show that the regular structure is represented by waves that drift along azimuth and have a clear spatial localization on considerable radius from plasma lens axis. Experimental results are in accordance with theoretical analysis showing an appearance of nonlinear electron vortices structures for these conditions.